Recommendations for neoadjuvant pathologic staging (ypTNM) of cancer of the esophagus and esophagogastric junction for the 8th edition AJCC/UICC staging manuals. Issue 8 (1st December 2016) - Rice, Thomas W.; Ishwaran, Hemant; Kelsen, David P.; Hofstetter, Wayne L.; Apperson‐Hansen, Carolyn; Blackstone, Eugene H.; ,
SUMMARY: We report analytic and consensus processes that produced recommendations for neoadjuvant pathologic stage groups (ypTNM) of esophageal and esophagogastric junction cancer for the AJCC/UICC cancer staging manuals, 8th edition. The Worldwide Esophageal Cancer Collaboration provided data for 22, 654 patients with epithelial esophageal cancers; 7, 773 had pathologic assessment after neoadjuvant therapy. Risk‐adjusted survival for each patient was developed. Random forest analysis identified data‐driven neoadjuvant pathologic stage groups wherein survival decreased monotonically with increasing group, was distinctive between groups, and homogeneous within groups. An additional analysis produced data‐driven anatomic neoadjuvant pathologic stage groups based only on ypT, ypN, and ypM categories. The AJCC Upper GI Task Force, by smoothing, simplifying, expanding, and assessing clinical applicability, produced consensus neoadjuvant pathologic stage groups . Grade and location were much less discriminating for stage grouping ypTNM than pTNM. Data‐driven stage grouping without grade and location produced nearly identical groups for squamous cell carcinoma and adenocarcinoma. However, ypTNM groups and their associated survival differed from pTNM. The need for consensus process was minimal. The consensus groups, identical for both cell types were as follows: ypStage I comprised ypT0‐2N0M0; ypStage II ypT3N0M0; ypStage IIIA ypT0‐2N1M0; ypStage IIIB ypT3N1M0, ypT0‐3N2, and ypT4aN0M0; ypStage IVA ypT4aN1‐2, ypT4bN0‐2, and ypTanyN3M0; and ypStage IVB ypTanyNanyM1. Absence of equivalent pathologic (pTNM) categories for the peculiar neoadjuvant pathologic categories ypTisN0‐3M0 and ypT0N0‐3M0, dissimilar stage group compositions, and markedly different early‐ and intermediate‐stage survival necessitated a unified, unique set of stage grouping for patients of either cell type who receive neoadjuvant therapy.